Fast Facts: Digital Medicine : Measurement - Coravos, Andrea; Goldsack, Jennifer C; Karlin, Daniel R; Nebeker, Camille; Perakslis, Eric; Zimmerman, Noah; Erb, M. Kelley (S. Karger, 2020)
Technology is changing how we practice medicine. Sensors and wearables are getting smaller and cheaper, and algorithms are becoming powerful enough to predict medical outcomes. Yet despite rapid advances, healthcare lags behind other industries in truly putting these technologies to use. A major barrier is the cross-disciplinary approach required to create digital tools, a process that requires knowledge from many people across a range of fields. 'Fast Facts: Digital Medicine – Measurement' aims to overcome that barrier, introducing the reader to core concepts and terms and facilitating dialogue. Contrasting 'clinical research' with routine 'clinical care', this short colorful book describes types of digital measurement and how to use and validate digital measures in different settings. And with the burgeoning development of digital medicine tools, the authors provide a timely overview of the security, ethical, regulatory and legal issues to be considered before a product can enter the market.Contents:• What is digital medicine? • Where does digital medicine fit? • Regulatory considerations• Ethical principles and our responsibilities• Ethics in practice• Security, data rights and governance• Digital biomarkers and clinical outcomes• Measurement in clinical trials• Verification and validation• The future of digital medicine
Keywords: Monitoring, Physiologic; Computing Methodologies; počítačové metodologie; monitorování fyziologických funkcí; individualizovaná medicína; lékařská informatika; Medical Informatics; Precision Medicine